f(x-f(y))=1-x-y

Simple and best practice solution for f(x-f(y))=1-x-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x-f(y))=1-x-y equation:


Simplifying
f(x + -1f(y)) = 1 + -1x + -1y

Multiply f * y
f(x + -1fy) = 1 + -1x + -1y

Reorder the terms:
f(-1fy + x) = 1 + -1x + -1y
(-1fy * f + x * f) = 1 + -1x + -1y

Reorder the terms:
(fx + -1f2y) = 1 + -1x + -1y
(fx + -1f2y) = 1 + -1x + -1y

Solving
fx + -1f2y = 1 + -1x + -1y

Solving for variable 'f'.

Reorder the terms:
-1 + fx + -1f2y + x + y = 1 + -1x + -1y + -1 + x + y

Reorder the terms:
-1 + fx + -1f2y + x + y = 1 + -1 + -1x + x + -1y + y

Combine like terms: 1 + -1 = 0
-1 + fx + -1f2y + x + y = 0 + -1x + x + -1y + y
-1 + fx + -1f2y + x + y = -1x + x + -1y + y

Combine like terms: -1x + x = 0
-1 + fx + -1f2y + x + y = 0 + -1y + y
-1 + fx + -1f2y + x + y = -1y + y

Combine like terms: -1y + y = 0
-1 + fx + -1f2y + x + y = 0

The solution to this equation could not be determined.

See similar equations:

| 15-(5x+8)=19+3x | | h^2+18h-8=0 | | (u+8)(u+4)=0 | | 5b-6-9b-8= | | P=5x-2(50+x) | | 1+2a-7+9a+5=6a+8a-13+2-3a | | 34/35:(x-3)=17/25:2/5 | | P=5x-(10+2x) | | 1/6(-12x-11)= | | 3v^2+4=8v | | 200=3x+2y | | 30=-5(6n+2) | | 12x-3(3x-2)=2x+10 | | X-4y=-44 | | R^2/d^2=gt | | 7=1d-3 | | 5x-0.02+x=19.98 | | 1/6/5/18=2/5/n | | 2y=60-3x | | 2xsquared+5x=7 | | (5b^2-15)/(b-3) | | indices8x=1/4 | | -68+(-2)= | | f(x)=2x^2+8x+9 | | 2x+(x+42)=90 | | 5/a*a | | 24x-13=4(6x-3)-1 | | 8x+13=-7x-18 | | 5x(2+8)= | | -0.25x^2+3.25x=y | | N:1/2 | | 8s=6/5 |

Equations solver categories